2019
DOI: 10.1530/joe-18-0686
|View full text |Cite
|
Sign up to set email alerts
|

The role of adipokines in developmental programming: evidence from animal models

Abstract: Alterations in the environment during critical periods of development, including altered maternal nutrition, can increase the risk for the development of a range of metabolic, cardiovascular and reproductive disorders in offspring in adult life. Following the original epidemiological observations of David Barker that linked perturbed fetal growth to adult disease, a wide range of experimental animal models have provided empirical support for the developmental programming hypothesis. Although the mechanisms rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 119 publications
(140 reference statements)
1
5
0
Order By: Relevance
“…Delayed onset of puberty corresponds with lowered birth weight. We observed that vaginal opening (Onset of puberty) in the protein-deficient models did not occur within the normal age range earlier reported by Picut et al (2015) , The diversity and progression of puberty have been linked to lowered birthweight ( Castellano and Tena-Sempere, 2016 ), this provides the basis for the fact that perinatal protein malnutrition is capable of programming the offspring's sexual maturity ( Reynolds and Vickers, 2019 )since epigenetic factors play a role in sexual development ( Bhandari et al, 2015 ). Burke et al (2017) , earlier stated that delayed onset of puberty may be inconsequential but the long-lasting differences associated with it may be detrimental, our result shows that the delayed puberty aligns with reduced fertility index in adults, therefore better-explaining fertility intricacies and pregnancy outcomes earlier reported in the F 1 generation.…”
Section: Discussionsupporting
confidence: 50%
“…Delayed onset of puberty corresponds with lowered birth weight. We observed that vaginal opening (Onset of puberty) in the protein-deficient models did not occur within the normal age range earlier reported by Picut et al (2015) , The diversity and progression of puberty have been linked to lowered birthweight ( Castellano and Tena-Sempere, 2016 ), this provides the basis for the fact that perinatal protein malnutrition is capable of programming the offspring's sexual maturity ( Reynolds and Vickers, 2019 )since epigenetic factors play a role in sexual development ( Bhandari et al, 2015 ). Burke et al (2017) , earlier stated that delayed onset of puberty may be inconsequential but the long-lasting differences associated with it may be detrimental, our result shows that the delayed puberty aligns with reduced fertility index in adults, therefore better-explaining fertility intricacies and pregnancy outcomes earlier reported in the F 1 generation.…”
Section: Discussionsupporting
confidence: 50%
“…Adipokines have an important biological role in regulating lipid metabolism (Reynolds and Vickers, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This perspective would consider aspects of childhood growth, adiposity and other known factors underpinning type 2 diabetes. Clare Reynolds and Mark Vickers (Reynolds & Vickers 2019) focus on this developmental aspect of adiposity, discussing the roles of leptin, adiponectin and other adipokines in rodent and large animal models and how they can be used to intervene with some of the disorders produced by developmental responses to nutritional insults. The original hypothesis proposed by Hales and Barker focused on impaired early fetal growth that may have been the result of poor nutrition, but these reviews also point to over-nutrition and maternal diabetes as potentially leading to developmental adaptations and later disease risk.…”
Section: Trassaneementioning
confidence: 99%